2023
DOI: 10.1002/ejic.202300188
|View full text |Cite
|
Sign up to set email alerts
|

β‐Alkylation through Dehydrogenative Coupling of Primary Alcohols and Secondary Alcohols Catalyzed by Thioether‐Functionalized N‐Heterocyclic Carbene Ruthenium Complexes

Abstract: A catalytic system for the direct β‐alkylation of secondary alcohol with primary alcohol has been investigated. In this work, a series of cationic Ru(II)(η6‐p‐cymene) complexes with thioether‐functionalized N‐heterocyclic carbene ligands (imidazole‐based 1 a–l and benzimidazole‐based 2 a–e) have been successfully synthesized and evaluated as catalysts. This investigation shows that modifications in the ligand moiety (thioether group and/or NHC core) have a strong effect on both selectivity and reactivity. Imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…The functionalisation of 2-mercapto-5-methyl-1,3,4-thiadiazole (1) with α,ωdihalogenoalkanes was performed by applying the one-step procedure shown in Scheme Sulphur-containing ligands, on the other hand, have shown remarkable coordination properties [54][55][56][57][58][59][60][61] and have displayed a wide range of applications [62][63][64][65][66][67][68]. Among them, heterocyclic thioethers have exhibited a broad spectrum of bioactivities [69][70][71][72] and efficiency as adsorbents for lead ion removal from water [73], ligands in N-heterocyclic carbene (NHC) complexes [74][75][76][77], metal-organic frame-works [78][79][80][81][82], etc. As a very particular example, it is shown that symmetrical bis-1,3,4-thiadiazole-containing bis-thioethers tune the framework formation of silver(I) coordination architectures [83].…”
Section: Resultsmentioning
confidence: 99%
“…The functionalisation of 2-mercapto-5-methyl-1,3,4-thiadiazole (1) with α,ωdihalogenoalkanes was performed by applying the one-step procedure shown in Scheme Sulphur-containing ligands, on the other hand, have shown remarkable coordination properties [54][55][56][57][58][59][60][61] and have displayed a wide range of applications [62][63][64][65][66][67][68]. Among them, heterocyclic thioethers have exhibited a broad spectrum of bioactivities [69][70][71][72] and efficiency as adsorbents for lead ion removal from water [73], ligands in N-heterocyclic carbene (NHC) complexes [74][75][76][77], metal-organic frame-works [78][79][80][81][82], etc. As a very particular example, it is shown that symmetrical bis-1,3,4-thiadiazole-containing bis-thioethers tune the framework formation of silver(I) coordination architectures [83].…”
Section: Resultsmentioning
confidence: 99%
“…34 As observed, the Ru-6 complex having a pendant thiazolyl group, Scheme 6 Ruthenium-catalysed cross b-alkylation of secondary and primary alcohols (ref. [30][31][32][33][34][35][36][37][38][39][40].…”
Section: B-alkylation Of Secondary Alcohols With Primary Alcoholsmentioning
confidence: 99%
“…Cationic Ru complexes comprising thioether-functionalized N-heterocyclic carbenes (k 2 -C,S)-Ru-(II)Z 6 -p-cymene (Ru-11) developed by Achard and co-workers were equally successful for b-alkylation of secondary alcohols. 40 Other ruthenium-based catalysts, such as Ru(II)-NHC complex (Ru-12) 41 and picolyl-functionalized NHC (Ru-13), were also efficiently utilized for the b-alkylation of secondary alcohols. 42 In both of these cases, catalytic protocols were employed for the tandem one-pot synthesis of flavan derivatives and plant-derived bio-active natural products (Scheme 7).…”
Section: B-alkylation Of Secondary Alcohols With Primary Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation